Semantic priming of bilingual subjects Arabic/French and monolingual French subject - Sassane, Ali (Universiti Putra Malaysia Press, 2016)
The purpose of this paper is to study the organization of mental lexicon in semantic memory through the presentation a list of imaged and abstract words to bilingual subjects of Arabic/French and monolingual French subjects. For this experience, the technique of semantic priming was used where to write the first three words that come into their mind. This technique revealed the existence of several types of semantic relations within the same semantic network. In addition, there was a positive association between the words "target" and the words mentioned by our subjects because the time allotted for the experiment was observed. On the other hand, the words were organized in terms of memory semantic categories by inclusion of a set of equivalent words according to the taxonomic model (Collins & Loftus, 1975; Collins & Quillian, 1969). Finally, the associative strength between different items reflected the connectionist model of Boutanquoi (2003), who taught that a unit is connected to others only if a significant number of topics are associated with it.